Modifications of the 26S proteasome during boar sperm capacitation - Zigo, Michal; Kerns, Karl; Sutovsky, Miriam; Sutovsky, Peter (Cell and tissue research, 2018)
Protein ubiquitination is a stable, reversible post-translational modification, targeting proteins for degradation/recycling by the 26S proteasome in a well-characterized enzymatic cascade. Studies have revealed the role of UPS in the regulation of fertilization, including sperm-zona pellucida interactions and the early event of sperm capacitation. The present study investigates the changes in proteasome compartmentalization, subunit composition and post-translational modifications during in vitro capacitation of fresh boar spermatozoa. We observed capacitation-dependent shedding of both 20S core and 19S regulatory particles from the acrosome that was associated with decreased plasma membrane integrity, independent of proteasomal inhibition. Subunits PSMA1-7 of the 20S core did not appear to undergo post-translational modifications during capacitation, based on invariant molecular masses before and after capacitation; however, we observed multiple PSMD4 forms of 19S regulatory particles (50, 53, 70, 115-140, 160 and >176 kDa) sequentially released from spermatozoa. PSMD4 subunit was found to be post-translationally modified during the course of capacitation, resulting in changes of apparent molecular mass, some of which were dependent on proteasomal inhibition. These results show that the sperm proteasomes are being modified during sperm capacitation. Additional studies of individual 26S proteasome subunits will be required to elucidate these modifications and to understand how UPS modulates sperm capacitation.
Keywords: PSMD4; průtoková cytometrie; Ubiquitin; Sperm Capacitation; PSMA1–7; Proteasome Endopeptidase Complex; mužské pohlaví; podjednotky proteinů; proteasomový endopeptidasový komplex; Boar; Flow Cytometry; Swine; Fertilization; Sperm capacitation; zvířata; kapacitace spermií; Protein Subunits; prasata; 26S proteasome; Male; Animals